Synopsis of colorectal cancer: prevalence, symptoms, screening, staging, risk factors, and treatment - Gehan F. Balata; Hany N. Azzam (The Egyptian Journal of Internal Medicine)
Abstract Colorectal cancer (CRC) impacts the colon and rectum, ranking as the fourth deadliest cancer worldwide, accounting for 10% of cancer cases and 9.4% of cancer-related deaths. CRC is frequently without symptoms until it reaches its later stages. Screening programs, including colonoscopies and tests on stool samples, have enhanced the chances of survival for people younger than fifty. The TNM staging system, which evaluates tumor size, lymph node involvement, and metastasis, is commonly utilized. Factors that increase the risk of developing colorectal cancer include exposure to chemicals, chronic inflammatory bowel disease, obesity, smoking, family history, genetic mutations, and specific diets. Diets high in fat, consumption of too much iron, sugary beverages, and meals with high sugar content can elevate the risk of CRC, whereas incorporating whole grains, fiber, calcium, vitamin D, dairy products, vegetables, fruits, and green tea into your diet can lower the risk. Management differs depending on stage: stages 0 and I are treated with endoscopy and local excision, whereas stages II, III, and IV necessitate systemic treatments like immunotherapy, targeted therapy, and chemotherapy.